2020
DOI: 10.1101/2020.10.28.20221259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CD64 and CD169 could help differentiate bacterial from viral infections in Emergency Department

Abstract: Background: The identification of a bacterial, viral or even non-infectious cause is essential in the management of febrile syndrome in the emergency department (ED) setting, especially in epidemic contexts such as flu or CoVID-19. Objectives: The aim of this study was to assess discriminative performances of two biomarkers, CD64 on neutrophils (nCD64) and CD169 on monocytes (mCD169), using a new flow cytometry procedure, in patients presenting with fever to the ED. Human leucocyte antigen-DR on monocytes (mH… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
(49 reference statements)
1
9
1
Order By: Relevance
“…In this group, both biomarker values were comparable with the observed in the HC group, pointing to the exclusive role of CD169Mo ratio as a marker for acute viral infection, which normalizes after infection chronicity. This assay has the potential to detect acute viral and bacterial coinfection when both CD64N and CD169Mo are increased ( 12 ), as observed in two cases of ACov-2 in our cohort.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In this group, both biomarker values were comparable with the observed in the HC group, pointing to the exclusive role of CD169Mo ratio as a marker for acute viral infection, which normalizes after infection chronicity. This assay has the potential to detect acute viral and bacterial coinfection when both CD64N and CD169Mo are increased ( 12 ), as observed in two cases of ACov-2 in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…The present work shows a cut-off value of 3.3 in both biomarkers, very similar to that described previously ( 14 ). However, this assay is not specific to ACov-2 infection since CD169Mo was increased in acute parainfluenza, human respiratory syncytial, and C-hepatitis virus infections at emergency units ( 12 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate diagnosis of bacterial or viral infection within 1 hour using flow cytometry was possible using a set of surface proteins on neutrophils and monocytes, including Fcg receptor I (FcgRI/ CD64), FcgRII/CD32, complement receptor 1 (CR1/CD35), HLA-class-I, and the receptor for complement-derived anaphylatoxin C5a (C5aR/CD88) (67). CD32, CD35 and CD88 all have a higher expression on both neutrophils and monocytes in bacterial infections compared to viral infections, whereas HLA-class-I and CD169 on monocytes were increased in viral infections rather than bacterial infections (71,72). These studies only included adults, no data on the pediatric population is available.…”
Section: Potential New Biomarkers For Infectionmentioning
confidence: 99%
“…It has been shown that monitoring the expression of CD169 on monocytes (mCD169), CD64 on neutrophils (nCD64), and HLA-DR on monocytes (mHLA-DR) by flow cytometry can be indicative of viral or bacterial infection, or sepsis, respectively. We therefore established a panel consisting of antibodies targeting these three markers and evaluated the one-step method in subjects with infection and septic conditions by measuring the expression of the three infection-related markers (Bourgoin et al, 2019a(Bourgoin et al, , 2019b(Bourgoin et al, , 2020a(Bourgoin et al, , 2020b(Bourgoin et al, , 2020c(Bourgoin et al, , and 2021Bedin et al, 2020;Michel et al, 2020).…”
mentioning
confidence: 99%